Carbene-catalyzed atroposelective annulation and desymmetrization of urazoles - Jin, Jiamiao (2022)
An NHC-catalyzed atroposelective reaction between ynals and urazoles is disclosed. The reaction establishes a chiral C-N axis via an atroposelective [3 + 2] annulation/desymmetrization process. Our reaction allows efficient access to axially chiral and heteroatom-rich urazole derivatives with potential applications in bioactive molecules and catalysis.